Computer‐mediated communication and social support among community‐dwelling older adults: A systematic review of cross‐sectional data. (4th August 2019) - Fuss, Belinda G.; Dorstyn, Diana; Ward, Lynn
Abstract: Objective: To systematically assess the relationship between computer‐mediated communication and social function in older adults aged 55 or older. Methods: Embase, PsycINFO and PubMed were searched (database inception to December 2018). Where available, effect sizes (correlation r) with 95% confidence intervals and P values were calculated for individual studies. Of 4, 139 eligible articles retrieved, 17 studies involving a pooled sample of 17, 640 participants were included. Results: Frequent computer‐mediated communication was significantly, albeit weakly, associated with higher levels of social support and connectedness ( r range = 0.08 to 0.33, P < 0.05). One discrepant negative relationship was noted ( r = −0.16, 95% CI [−0.30, −0.02], P = 0.03), involving a distinct sample of gamers. Conclusions: Computer‐mediated communication is related to amount of social functioning in older adults, although the causal nature of this relationship requires further longitudinal investigation. Sample confounds (eg socio‐economic status and successful ageing) may limit the interpretation of these findings.